Préhistoires de l'écriture - Graff, Gwenola; Jiménez Serrano, Alejandro (Préhistoires de la Méditerranée, 2016)
The genesis of early writing has generated a geat deal of interest and is often misunderstood. The goal of this scientific meeting was to gather scholars working on different graphical systems attested during the 4th millenium BCE in Egypt. Different material supports have been taken into account for this period, in Egypt and with comparisons in Mesopotamia. The authors also investigate the link between image and writing, the social and cultural contexts within which this transformation occured and the status of the sign. Indeed, it seems that the relation between the sign and the material support might be a key of understanding. Several promising avenues have been pinpointed while taking into account of the memorization techniques of oral performance in ritual practice.